1988
DOI: 10.1200/jco.1988.6.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Very-high-dose cisplatin and etoposide in children with untreated advanced neuroblastoma.

Abstract: Between January and December 1985, 17 children with advanced neuroblastoma who were greater than 1 year old (16 stage IV, one stage III) were administered cisplatin (CPDD, 200 mg/m2) and etoposide (VP-16, 500 mg/m2) as a pilot study of toxicity and response rates for the European Neuroblastoma Study Group (ENSG). The study was designed to assess toxicity of two courses of treatment, and evaluate response rates after this short therapy. The creatinine clearance declined in seven of 15 patients. No patient exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(17 citation statements)
references
References 16 publications
1
14
0
2
Order By: Relevance
“…With the high doses of platinum compounds used, a dose-effect relationship has already been shown. 21,22,36 The response rates we observed with these conventional regimens are within the ranges already published. Only 34% of patients entered CR or VGPR following first-line chemotherapy (good responders).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…With the high doses of platinum compounds used, a dose-effect relationship has already been shown. 21,22,36 The response rates we observed with these conventional regimens are within the ranges already published. Only 34% of patients entered CR or VGPR following first-line chemotherapy (good responders).…”
Section: Discussionsupporting
confidence: 74%
“…The protocols used for conventional chemotherapy, which have previously been published, were mostly a combination of vincristine, cyclophosphamide, doxorubicin, etoposide or teniposide, cisplatinum or carboplatin. [20][21][22] High-dose chemotherapy During these two decades, several high-dose drug combinations were used. Throughout the period, all combinations contained high-dose melphalan, 140 to 180 mg/m 2 , and approximately 50% of patients were treated with a busulfan-containing regimen.…”
Section: Primary Therapymentioning
confidence: 99%
“…[5][6][7][8][9]38,39 Significant concerns regarding the longterm toxicity of cisplatin and bleomycin [11][12][13][14][15] delayed the introduction of cisplatin-based therapy in pediatric patients. After pediatric Phase II studies suggesting that high-dose cisplatin was effective and tolerable in patients with solid tumors and neuroblastoma, 23,24 the POG/CCG Intergroup Germ-Cell Tumor Subcommittee designed a randomized study to evaluate the effect of cisplatin dose intensity on outcome. 25 Unlike the adult study, 7 the pediatric study revealed that using HDPEB improved EFS significantly for pediatric patients with advanced GCT.…”
Section: Discussionmentioning
confidence: 99%
“…Further, German investigators developed a risk-based approach to PGCT that incorporated the use of both cisplatin and ifosfamide. 18 -20 The adult data suggesting that high-dose cisplatin, etoposide, and bleomycin (HDPEB) was more effective than PEB, 21,22 along with the reports suggesting that high-dose cisplatin was efficacious and had acceptable toxicity, 23,24 prompted the Pediatric Oncology Group (POG) and Children's Cancer Group (CCG) to evaluate the impact of cisplatin dose intensity on outcome. The results of that study revealed that unlike in adults with testicular tumors, 7 HDPEB significantly improved the EFS for children with advanced GCT.…”
mentioning
confidence: 99%
“…High response rates in relapsed patients had been reported several years ago, using conventional dose cisplatinum in combination with VM26 (Hayes et al, 1981), and the demonstration in adults with germ cell tumours that considerable dose escalation of cisplatin was possible if the drug was given in divided doses encouraged enthusiam about this approach in neuroblastoma. Fortunately, children are much less prone to the often crippling peripheral neurotoxicity of high dose cisplatin seen in adults and this regimen was well tolerated in phase III studies (Hartmann et al, 1988). Ifosfamide/adriamycin and high dose platinum/VP16 produces rapid clearing of metastatic disease and, with surgery, produces CR rates around 60% (Pinkerton et al, 1990).…”
mentioning
confidence: 99%